PENGARUH TINGKAT PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL ALILA SEMINYAK - Ni Luh Made Wijayati; I Wayan Sukarta; Ni Nyoman Supiatni; Ni Putu Dewanthy Paramitha Dewi (STIMI Handayani Denpasar, 2022)
This study aims to determine: (1) the effect level of education on employee performance at the Alila Seminyak Hotel, (2) the effect of work experience on employee performance at the Alila Seminyak Hotel, (3) the effect of education level and work experience together on employee performance at Alila Hotel Seminyak. Sampling was conducted at permanent employees of the Alila Seminyak Hotel by using a random sampling method with a total sample of 76 people. The research method used is a quantitative method. Data analysis technique used to answer hypotheses is multiple linear regression analysis techniques using SPSS (Statistical Product and Service Solution). The results of this study indicate that: (1) the level of education has a positive and significant effect on employee performance at the Alila Seminyak Hotel, evidenced from the tcount of 4.473 and a significance value of 0.000 <0.05. (2) work experience has a positive and significant effect on employee performance at the Alila Seminyak Hotel, evidenced from the tcount of 3.659 and a significance value of 0.000 <0.05. (3) the level of education and work experience simultaneously has a positive and significant effect on employee performance at the Alila Seminyak Hotel, as evidenced by the test results obtained by Fcount of 93,387 with a probability level of 0,000 which is far below alpha 5%.